Caracterização de arranjos de aterramento através de medições no domínio do tempo - Carlos Ermídio Ferreira Caetano (2019)
A set of concepts capable of defining a new perspective for grounding arrangements characterization is developed. It is based on three distinct and totally innovative measurement proposed methods. Initially, a survey of the subject is presented, including pioneer work and the most recent publications. A new method of measuring the grounding resistance is then described. It is based on the measured net charge drained by the grounding system when excited by a pulse generator. The theorem that supports the method has been recently published. It is briefly described, along with the method itself. An advantage of this method with respect to the traditional ones is that it is not affected by the self and mutual impedance of the grounding system and in the measuring cables. Moreover, the proposed method does not require the measurement of surface potentials, which are prone to interference due to soil non-homogeneity, buried conductive bodies, and stray currents. Additionally, a method of grounding impedance measurement is presented. It can be understood as a result of the proposed resistance measurement method, since the conceptual core of both is based on the same measurement arrangement. The impedance measurement method uses only currents flowing through the grounding, i.e. it also does not require the measurement of surface potentials, which are prone to interference due to soil non-homogeneity, buried conductive bodies, and stray currents. The final chapter presents a methodology dedicated to the characterization of the impulse response of grounding arrangements, based on the measured curves, either by the traditional methods (relation between voltage and current waveforms) or by the proposed method of measuring impedance (current waveforms only). From the measurement curves using impulsive waves, the methodology determines a non-parametric grounding model, which can be used to reconstruct the response of this grounding system to any exciting wave. Theoretical and experimental validation results are presented throughout the whole work using real grounding arrangements in low and high resistivity soils. The results show that the methods provide consistent and accurate values of grounding resistance and impedance, as well as a safe procedure for the characterization of the tested arrangements.